2004
DOI: 10.1007/s11746-004-0894-7
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of tea theaflavins and methylated catechins in canola oil

Abstract: The present study examined the antioxidant activity of black tea theaflavins and catechin derivatives in canola oil. Oxidation was conducted at 95°C by monitoring the oxygen consumption and decreases in the linoleic and α-linolenic acids of canola oil. All were tested at a concentration of 0.5 mM. Catechins, including (-)-epicatechin, (-)-epicatechin gallate, (-)-epigallocatechin, and (-)-epigallocatechin gallate (EGCG), were more effective than theaflavins, namely, theaflavin-1, theaflavin-3-gallate, theaflav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…Although the structure‐antioxidant activity relationship of flavonoids has been well defined in hydrophilic systems , studies dealing with this in hydrophobic systems are scarce. Free flavonoids, mainly quercetin, myricetin, morin, (+)catechin, (−)epigallocatechin, (−)epicatechin, and kaempferol, have been incorporated in different lipid systems with varying degrees of success in terms of oxidative stability, such as methyl linoleate , canola oil , cottonseed oil , corn oil , or fish oil . The antioxidant activity found in methyl linoleate and purified sunflower oil was related to the number of phenolic hydroxyl groups, 2,3 double bond in the C‐ring and a glycoside moiety in the molecule .…”
Section: Introductionmentioning
confidence: 99%
“…Although the structure‐antioxidant activity relationship of flavonoids has been well defined in hydrophilic systems , studies dealing with this in hydrophobic systems are scarce. Free flavonoids, mainly quercetin, myricetin, morin, (+)catechin, (−)epigallocatechin, (−)epicatechin, and kaempferol, have been incorporated in different lipid systems with varying degrees of success in terms of oxidative stability, such as methyl linoleate , canola oil , cottonseed oil , corn oil , or fish oil . The antioxidant activity found in methyl linoleate and purified sunflower oil was related to the number of phenolic hydroxyl groups, 2,3 double bond in the C‐ring and a glycoside moiety in the molecule .…”
Section: Introductionmentioning
confidence: 99%
“…86 Similarly, O-methylation at position C-3 0 in (À)-epicatechin, (À)-epigallocatechin and (À)-epicatechin-3-O-gallate elicited a potential inhibition of lipid oxidation of canola oil in comparison to the aglycone. 87 In a recent study, C-3 0 and C-4 0 -O-methyl ethers of (+)-catechin and (À)-epicatechin showed a lower antioxidant capacity than the parent compound, as measured by the ferric-reducing power (FRAP) and by the ability to scavenge the ABTS + radical cation.…”
mentioning
confidence: 99%
“…Since the hydroxyl substitutions play an important role in antioxidative activity, the level of antioxidative activity appeared related to the number of them, and we previously reported a similar trait on radical-scavenging activity (Tabata et al, 2008). It has also been noted that methylated derivatives of catechines have a lower protective activity against lipid oxidation than their corresponding precursors (Su et al, 2004). Since the physiological concentration of phenolic compounds is less than a few lM, our results suggest that the M. japonicus leaf antioxidative component of mallotinic acid, mallotusinic acid, corilagin, and geraniin can protect intracellular and extracellular components against oxidative stress under the physiological conditions.…”
Section: Discussionmentioning
confidence: 73%